Nők és helyzetük az iszlám világában - Balázs, Judit (Acta Scientiarum Socialium, 2017)
Women and Their Position in the Islamic World.In the European culture a lot of misbeliefs prevail about Islam and especially about the place and situation of women in the Islamic world. According to one such opinion, the woman is only a source of pleasure; in another opinion, they are soulless objects and their only function is to work for the family. The present study is an attempt to highlight this duality and to create an objective picture. The main areas of the research are marriage, sexual life, the right to work (or the lack thereof), family life, and child care. In this analysis the author tries to explain and interpret institutions, facts and situations in the Islamic word which are hard to understand for Europeans, for example polygamy. A comparison is made between the positions of the Arabic and the Turkish women. The study also indicates that the interpretation and implementation of Islamic law differs from country to country in spite of the fact that the Islamic world is held as a homogenous, uniform one. However, many compulsory living habits are ascribed to Islam, although these „legal regulations” are not even mentioned in the Islamic holy book the Quran.
Keywords: women's rights; marriage; sexuality; prostitution; regulations of the Quran